Dietary lysine and slaughter weight affect growth performance and carcass characteristics in boars and barrows - Rantanen, M.M.; Hines, Robert H.; Kim, I.H.; Friesen, K.G.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
During the growing and finishing period, the boars ate less, had better F/G, and were less fat than barrows. A high plane of nutrition (high vs moderate lysine concentrations for the growing-finishing phases) and decreasing slaughter weight from 260 to 220 lb also improved efficiency of gain and carcass leanness. However, many notable interactions occurred among the gender x lysine x slaughter weight treatments. Also, year (rotational-cross of average health status and lean growth potential vs a terminal-cross of high lean growth potential after repopulation of the farm) had pronounced effects on growth performance and carcass merits such that the combination of lean genotype-boars-high lysine-220 lb had advantages of 15, 20, 39,49, and 15% for ADG, ADFI, and F/G, avg backfat thickness, and fat-free lean index, respectively, compared to the control (i.e., the avg lean growth-barrows-moderate lysine-260 lb treatment).
Keywords: Swine; Barrows; Boars; Genotype; Slaughter weight